Investigating the Determinants of Green Loyalty: Understanding Factors Influencing Customer Commitment to Sustainable Brands in Indonesia - Journey Firdausy Arasyi; Kusumawati, Nurrani (Journal of Consumer Studies and Applied Marketing, 2023)
In recent decades, the global emphasis on ecological sustainability and green marketing has revolutionized consumer preferences and behaviour. As businesses strive to meet the growing demand for eco-friendly products and services, understanding and assessing customer green loyalty have become pivotal objectives for sustained success. This research investigates the determinants of customers' green loyalty towards environmentally conscious goods and/or services. To achieve this objective, a quantitative analysis approach was adopted. A questionnaire-based survey was conducted using Google Forms, targeting 238 respondents. The collected data was subjected to descriptive statistics and partial least squares structural equation modelling (PLS-SEM) for comprehensive analysis. The findings of this study underscore the significant influence of two crucial factors - green trust and green image - on customers' green loyalty. The positive relationship between green trust and green loyalty highlights the importance of establishing trust in eco-friendly brands. Additionally, the positive impact of green image signifies the role of a brand's environmental reputation in fostering customer loyalty. These insights hold paramount importance for both theory and practice, shedding light on customers' loyalty patterns towards green brands in Indonesia. As businesses navigate the dynamic landscape of sustainability-driven consumer preferences, this research can guide strategic marketing efforts and promote eco-friendly practices to attract and retain loyal customers.